ANALISIS TINDAK TUTUR EKSPRESIF DALAM WACANA STAND UP COMEDY INDONESIA SESI 3 BABE CABITA DI KOMPAS TV - Risang Krista Pratama; Asep Purwo Yudi Utomo (CARAKA, 2020)
Expressive speech act is a type of speech act that states something that is felt by the speaker. This research is a descriptive study which in the end result tries to describe the object in accordance with the existing picture. This research uses a qualitative approach by applying descriptive qualitative methods. The data of this research is in the form of discourse Babe Cabita Stand Up Comedy Indonesia session 3 on Kompas Tv with Youtube page source, humorous speech acts used by the speaker to express things intended to be conveyed to the speech partners in this case is the audience. which is to be achieved to analyze expressive or evaluative speech acts in the Stand Up Comedy Indonesia discourse session 3 Babe Cabita in Kompas Tv. The results of the research show that there are several types of expressive or evaluative speech acts. In this study, the results of four types of expressive speech acts in humorous Indonesian Stand Up Comedy discourse session 3 Babe Cabita in Kompas Tv, namely: (1) expressive speech acts criticize, (2) expressive speech acts complaining, (3) expressive speech acts praise, (4) expressive speech acts of blame, and (5) speech acts of derogatory expressions. It is expected that the results of this study can be useful for readers who want to find references and for learning research in terms of pragmatic science, especially regarding expressive speech acts in subsequent research.